2021
DOI: 10.1155/2021/8105516
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Evaluation of the Effect of Bedside Ward Round Checklist on Clinical Outcomes of Critical Patients

Abstract: Objective. To systematically evaluate the effect of bedside ward round checklists on the clinical outcomes of critical patients and thus provide a scientific and rational basis for decision-making in its clinical application. Methods. PubMed, EMBASE, Web of Science, Cochrane Library, CNKI, and Wanfang databases were searched to collect the literature studies about randomized controlled trials (RCTs) and cohort studies involving the effect of bedside ward round checklists on the clinical outcomes of critical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…The systematic reviews on the ICDSC, a delirium screening checklist, were supportive of its use following the assessment of its validity [9,[42][43][44][45][46]. One systematic review on bedside ward round checklists found significant improvements in ICU length of stay (ICU LOS) and mechanical ventilation (MV) duration which were also the two most improved clinical outcomes identified by our scoping review [47]. The systematic reviews on handover checklists affirmed the improvements in information transfer and omissions found in our review [48].…”
Section: Ics and Ficm Percutaneous Tracheostomy Checklist [30] Yessupporting
confidence: 59%
See 2 more Smart Citations
“…The systematic reviews on the ICDSC, a delirium screening checklist, were supportive of its use following the assessment of its validity [9,[42][43][44][45][46]. One systematic review on bedside ward round checklists found significant improvements in ICU length of stay (ICU LOS) and mechanical ventilation (MV) duration which were also the two most improved clinical outcomes identified by our scoping review [47]. The systematic reviews on handover checklists affirmed the improvements in information transfer and omissions found in our review [48].…”
Section: Ics and Ficm Percutaneous Tracheostomy Checklist [30] Yessupporting
confidence: 59%
“…To our knowledge, this is the first published scoping review on the use and efficacy of checklists within the ICU but other reviews on related topics have previously been published [9,10,[41][42][43][44][45][46][47][48][49]. We identified one other scoping review on quality improvement tools for the nursing care of long stay patients in the ICU [41].…”
Section: Ics and Ficm Percutaneous Tracheostomy Checklist [30] Yesmentioning
confidence: 99%
See 1 more Smart Citation
“…We based this implementation in several papers that have been published reinforcing the value of checklists during ward rounds. Wen et al investigated the role of these and concluded that the checklist can be used to quickly identify the focus of quality inspection and could reduce the incidence of unexpected adverse events (17). Speci cally, another study concluded that checklist-based prompting improved multiple processes of care, including reported improvement in mortality and length of stay in their cohort, reducing errors of omission.…”
Section: Discussionmentioning
confidence: 99%
“…We based this implementation on several papers that have been published reinforcing the value of checklists during ward rounds. Wen et al investigated the role of these and concluded that the checklist can be used to quickly identify the focus of quality inspection and could reduce the incidence of unexpected adverse events [ 17 ]. Specifically, another study concluded that checklist-based prompting improved multiple processes of care, including reported improvement in mortality and LOS in their cohort, reducing errors of omission.…”
Section: Discussionmentioning
confidence: 99%